2022
DOI: 10.3390/cancers14235949
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Adult Post-Transplant Lymphoproliferative Disorder

Abstract: PTLD is a rare but severe complication of hematopoietic or solid organ transplant recipients, with variable incidence and timing of occurrence depending on different patient-, therapy-, and transplant-related factors. The pathogenesis of PTLD is complex, with most cases of early PLTD having a strong association with Epstein–Barr virus (EBV) infection and the iatrogenic, immunosuppression-related decrease in T-cell immune surveillance. Without appropriate T-cell response, EBV-infected B cells persist and prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 146 publications
0
4
0
Order By: Relevance
“…Studies have previously suggested that early-onset PTLD portends a better prognosis, better response to reduced immunosuppression, and improved overall survival compared to late-onset PTLD [52]. The advent of the CD20 inhibitor, rituximab, has led to significantly improved remission rates in SOT recipients, with complete remission seen at 87% in patients treated with rituximab in kidney transplant recipients.…”
Section: Viral Infectionsmentioning
confidence: 99%
“…Studies have previously suggested that early-onset PTLD portends a better prognosis, better response to reduced immunosuppression, and improved overall survival compared to late-onset PTLD [52]. The advent of the CD20 inhibitor, rituximab, has led to significantly improved remission rates in SOT recipients, with complete remission seen at 87% in patients treated with rituximab in kidney transplant recipients.…”
Section: Viral Infectionsmentioning
confidence: 99%
“…12 In 2016, the World Health Organization classified PTLD into four major histological subtypes; namely early lesions, polymorphic and monomorphic PTLD, and classic Hodgkin-type lymphoma. 7,13 There are currently no definitive preventative strategies for PTLD, and prophylactic antivirals may only have a role during the early lytic stages of EBV infection. 14 The aim of this study was to determine the prevalence, complications, and associated factors for developing PTLD in South African PLT recipients.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical spectrum of PTLD in children varies from being asymptomatic to disease presenting with florid symptoms including fever, diarrhea, and acute sepsis syndrome 12 . In 2016, the World Health Organization classified PTLD into four major histological subtypes; namely early lesions, polymorphic and monomorphic PTLD, and classic Hodgkin‐type lymphoma 7,13 …”
Section: Introductionmentioning
confidence: 99%
“…Post-transplant lymphoproliferative disorder (PTLD) is a major complication after solid organ transplantation (SOT) [ 1 ]. While immunosuppressive therapy has been associated with early Epstein-Barr virus (EBV) driven PTLD, late-onset PTLD often lack EBV and have more genomic aberrations [ 2 4 ]. Diagnosis of PTLD is challenging due to its variable presentation.…”
mentioning
confidence: 99%